2015
DOI: 10.1177/1933719114534536
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Endometrial Nerve Fibers in the Pathogenesis of Pain During Endometrial Biopsy at Office Hysteroscopy

Abstract: We aimed to evaluate whether nerve fibers are present in the endometrial layer of patients submitted to office hysteroscopy and their potential contribution to the pathogenesis of pain during that procedure. Through a prospective case-control study performed in tertiary centers for women's health, endometrium samples were collected during operative office hysteroscopy from 198 cycling women who previously underwent laparoscopy and/or magnetic resonance imaging investigation for infertility assessment. Samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
2
16
0
5
Order By: Relevance
“…Di Spiezio Sardo и соавт. [21]. Авторы исследовали экспрессию панели маркеров нервных волокон в эндометрии у женщин с и без эндометриоза/аденомиоза, у которых боль была более 5 баллов по шкале ВАШ.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Di Spiezio Sardo и соавт. [21]. Авторы исследовали экспрессию панели маркеров нервных волокон в эндометрии у женщин с и без эндометриоза/аденомиоза, у которых боль была более 5 баллов по шкале ВАШ.…”
Section: Discussionunclassified
“…Метаанализ биомаркеров эндометрия для оценки роли боли у больных с эндометриозом установил VIP как «перспективный маркер для дальнейшего исследования» [21].…”
unclassified
“…Studies have shown that women with endometriosis and pain have growths with greater nerve fiber density than woman with endometriosis without pain (Di Spiezio Sardo et al, 2015; Yao et al, 2010). In another study, a positive correlation was found between pain severity and cyst nerve fiber density (Mechsner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the growth's sprouted sensory and sympathetic nerve supply opens a two-way line of communication between the growths and CNS that is capable of generating pain (Stratton and Berkley, 2011). Studies in the rodents (Alvarez et al, 2012; McAllister et al, 2009, 2012) and a few clinical studies support this hypothesis (Di Spiezio Sardo et al, 2015; Mechsner et al, 2009; Wang et al, 2010). …”
Section: Introductionmentioning
confidence: 96%
“…Fibras nervosas têm expressão na camada funcional do endométrio e podem contribuir para o estímulo doloroso durante a manipulação da cavidade (46). Estudos atuais, revisionais, já publicados ou em andamento, associam injúria endometrial à dor como efeito adverso (37,(47)(48)(49), e suas consequências, inclusive o reflexo vasovagal (40).…”
Section: Efeitos Adversosunclassified